Primary Pediatric Cutaneous T-Cell Lymphoproliferative Disorders: 3 New Cases. Issue 3 (April 2018) - Guerzoni, Maria E.; Pruccoli, Federica; Palazzi, Giovanni; Mariotti, Ilaria; Cano, Carmen; Cellini, Monica; Cesinaro, Anna M.; Mataca, Ema; Iughetti, Lorenzo
Abstract : Primary cutaneous lymphoproliferative disorders are a composite group of diseases with considerable differences in histopathologic, immunophenotypic, and clinical features. They are exceedingly rare in children and in the literature only few cases are reported with extremely different therapeutic approaches. Because of the rarity of cutaneous lymphomas we consider crucial to increase the knowledge of these diseases providing every single case. We present 3 pediatric cases of primary cutaneous T-cell lymphomas occurred to our center with different features and therapeutic approach.